The Effect of Pilates Exercise on Low Back Pain in Pregnant Women in the Second and Third Trimesters at Edelweiss Day Spa - Agustina, Lusinta; Paryono, Paryono (Genius Midwifery Journal, 2024)
Objective: This study aims to determine the effect of Pilates Exercise on Low Back Pain in pregnant women in the second and third trimesters. Method: Type of quantitative research with a pre-experimental design with a one-group pretest-posttest design. The purposive sampling technique obtained a total sample of 32 respondents from pregnant women in the second and third trimesters. Results: After doing Pilates exercise, there were 27 respondents with mild pain (84.4%) and 5 respondents in the no pain category (15.6%). The results of the Wilcoxon Signed Rank Test show a p-value of 0.000, so p<0.05 so that Ha is accepted, which means there is an effect of Pilates exercise on the Low Back Pain of pregnant women in the second and third trimesters at Edelweiss Day Spa Klaten. Conclusion: There is an effect of Pilates exercise on the low back pain of pregnant women in the second and third trimesters at Edelweiss Day Spa Klaten